Non–vitamin K oral anticoagulants in hypertrophic cardiomyopathy patients undergoing catheter ablation of atrial fibrillation. (20th July 2020) - Creta, Antonio; Hunter, Ross J.; Earley, Mark J.; Finlay, Malcolm; Dhinoja, Mehul; Sporton, Simon; Chow, Anthony; Mohiddin, Saidi A.; Boveda, Serge; Adragao, Pedro; Jebberi, Zeynab; Matos, Daniel; et al.
Abstract: Introduction: Patients with hypertrophic cardiomyopathy (HCM) and atrial fibrillation (AF) require chronic anticoagulation due to high thromboembolic risk. Evidence supporting the use of non–vitamin K oral anticoagulants (NOACs) in patients with HCM remains sparse, and there are no data regarding the use of NOACs in patients with HCM undergoing catheter ablation of AF. Methods: Observational nonrandomized study in four European centers. We aimed to investigate the safety and efficacy of NOACs compared with vitamin K antagonists (VKAs) in patients with HCM undergoing catheter ablation for AF. Results: A total of 137 patients with HCM (mean age: 55.0 ± 13.4, 29.1% female) underwent 230 catheter ablations for AF (1.7 ± 1.0 per patient). A total of 55 patients (39.4%) underwent 70 procedures (30.4%) on NOAC, while the remaining were on VKA. Warfarin (97.6%) and rivaroxaban (56.4%) were the most frequently used agents in the respective groups. No procedure‐related deaths were reported. We observed no significant difference in the rate of thromboembolism (VKA: 0.6%; NOAC: 0%; p  = 1.0) or minor bleeding (VKA: 0.6%; NOAC: 1.4%; p  = .54). There was a nonsignificant trend towards a lower incidence of major bleeding (VKA: 6.9%; NOAC: 1.4%; p  = .09). Conclusion: These preliminary data suggest that NOACs are at least as safe and effective as VKAs in patients with HCM undergoing catheter ablation for AF.